2012
DOI: 10.1155/2012/813650
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy for Mildly Obese Patients (Body Mass Index of 30 <35 kg/m2): Operative Outcome and Short-Term Results

Abstract: Background. Data concerning laparoscopic sleeve gastrectomy (LSG) in mild obesity are under investigation. Aim/Objective. May 2010 to May 2012, 122 consecutive patients with preoperative body mass index (BMI) of 33 ± 2.5 kg/m2 (range 30–34.9) undergoing LSG were studied. Mean age was 33 ± 10 years (range 15–60), and 105 (86%) were women. Mean preoperative weight was 91 ± 9.7 kg (range 66–121), and preoperative excess weight was 30 ± 6.7 kg (range 19–43). Comorbidities were detected in 44 (36%) patients. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
3
6
0
1
Order By: Relevance
“…We have previously performed a series of LSG in patients with BMI 30-35 kg/m 2 and evaluated short-term risks and benefits. LSG was technically straightforward and resulted in excellent outcomes without substantial surgical risks [10]. The current series confirms our previously published results in the short and long term and outlines the absence of high gastric leak in this population when LSG is performed by experienced surgeons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have previously performed a series of LSG in patients with BMI 30-35 kg/m 2 and evaluated short-term risks and benefits. LSG was technically straightforward and resulted in excellent outcomes without substantial surgical risks [10]. The current series confirms our previously published results in the short and long term and outlines the absence of high gastric leak in this population when LSG is performed by experienced surgeons.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to other authors, we have previously reported excellent outcomes without any substantial surgical risks in patients with BMI 30-35 kg/m 2 undergoing LSG [10,11]. Although, the major advantage of LSG is technical simplicity, gastric leaks can occur and remain a dreaded and lifethreatening complication [12,13].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…But LSG is not complication-free at all and one of the major postoperative complication is still the staple line leak, which occurs in approximately 2.2-2.4% of patients [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. There are various factors which influence the risk of leak.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it has been accepted as a definitive stand-alone procedure due to the excellent results in terms of excess weight loss (%EWL) and control of comorbidities, with significant 3 and 5-year experiences that justify this recommendation [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%